Wills, Executors, and Trustees (Book). - Cannon, Arthur M.; Thompson, George C. (The Accounting Review, 1951)
Reviews the book "Wills, Executors, and Trustees," by William J.Grange, Walter R.Staub and Eugene G.Blackford.